Yersinia enterocolitica in Italy: A Case of Septicemia and Abdominal Aortic Aneurysm Infection - Rodio, Donatella M.; Bressan, Alessia; Ambrosi, Cecilia; Scribano, Daniela; Tolli, Rita; Mansour, Wassim; Speziale, Francesco; Antonelli, Guido; Trancassini, Maria; Pietropaolo, Valeria (Frontiers in Medicine, 2018)
We report a case of Yersinia enterocolitica septicemia in a 63-year-old patient admitted to the Vascular Surgery Department of Umberto I Hospital (Rome, Italy) for an abdominal aortic aneurysm. The microorganism, recovered from both peripheral blood cultures and aneurysmatic aortic wall specimens, was identified as Y. enterocolitica using matrix-assisted laser desorption ionization–time of flight analysis (MALDI-TOF MS) and 16S rDNA gene sequencing. The isolate responsible for septicemia belonged to the O:9 serotype (biogroup 2). A genetic screening of the isolate made it possible to detect the presence of both the yst and ail genes, encoding a heat-stable enterotoxin and a protein involved in invasion/adherence and serum resistance, respectively. Our case contributes in enriching epidemiological data concerning Y. enterocolitica infections, which might represent severe complications in patients suffering from cardiovascular diseases. Moreover, this study, together with the others, should be regarded as valuable and useful tools for monitoring the rate of infections worldwide.